1996
DOI: 10.1017/s0950268800052675
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recent toxoplasma infection in pregnant women in Naples

Abstract: SUMMARYEffective primary prevention of congenital toxoplasmosis requires up to date information on locally relevant risk factors for infection in pregnant women. In Naples, risk factors for toxoplasma infection were compared in recently infected women (as assessed by detection of specific IgM in serum) and susceptible, IgG negative women. Recent infection was strongly associated with frequency of consumption of cured pork and raw meat. Eating cured pork or raw meat at least once a month increased the risk of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
3
10

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 14 publications
5
49
3
10
Order By: Relevance
“…Cook et al conducted a European multi-centre study in pregnant women where the risk factors most strongly predictive of acute infection were eating undercooked lamb, beef or game, contact with soil, and travel outside Europe and the United States and Canada [12]. Buffolano et al found an association between recent infection in pregnant women in Italy and consumption of cured pork and raw meat (of unspecified type) [13]. Kapperud et al discovered associations between increased risk of maternal infection and a large number of factors including (among others) undercooked minced meat products, undercooked mutton, undercooked pork and cleaning cat litter boxes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al conducted a European multi-centre study in pregnant women where the risk factors most strongly predictive of acute infection were eating undercooked lamb, beef or game, contact with soil, and travel outside Europe and the United States and Canada [12]. Buffolano et al found an association between recent infection in pregnant women in Italy and consumption of cured pork and raw meat (of unspecified type) [13]. Kapperud et al discovered associations between increased risk of maternal infection and a large number of factors including (among others) undercooked minced meat products, undercooked mutton, undercooked pork and cleaning cat litter boxes [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Southern region, where this study was conducted, has a low prevalence of toxoplasmosis among pregnant women (Nobrega & Karnikowski 2005, Figueiro-Filho et al 2007. However, there is substantial variability in the reported data, depending on chosen population, diagnostic methods used in screening, or even the different risk factors involved in disease transmission (Buffolano et al 1996, Kapperud et al 1996, Cook et al 2000, Jones et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence in most countries varies from 20% to 80% -about 20% of pregnant women in Finland (Lappalainen et al 1992), 27% in Denmark (Lebech et al 1993), 40% in southern Italy (Buffolano et al 1996), and 84% in Paris (Desmonts and Couvreur 1974). Four different forms of this parasitosis exist.…”
mentioning
confidence: 99%